Re-induction ipilimumab following acquired resistance to combination ipilimumab and anti–PD-1 therapy. (August 2021) - Hepner, Adriana; Atkinson, Victoria G.; Larkin, James; Burrell, Rebecca A.; Carlino, Matteo S.; Johnson, Douglas B.; Zimmer, Lisa; Tsai, Katy K.; Klein, Oliver; Lo, Serigne N.; Haydon, Andrew; Bhave, Prachi; et al.
Abstract: Purpose: Combination immunotherapy with nivolumab and ipilimumab has a high initial response rate in advanced melanoma; however, up to 55% of patients later progress. The efficacy and safety of ipilimumab re-induction in the setting of acquired resistance (AR) to combination immunotherapy is unknown. Methods: Patients with advanced melanoma who initially achieved a complete response, partial response or sustained stable disease to induction combination immunotherapy then progressed and were reinduced with ipilimumab (alone or in combination with anti–PD-1) and were analysed retrospectively. Demographics, disease characteristics, efficacy and toxicity were examined. Results: Forty-seven patients were identified from 12 centres. The response rate to reinduction therapy was 12/47 (26%), and disease control rate was 21/47 (45%). Responses appeared more frequent in patients who developed AR after ceasing induction immunotherapy (30% vs. 18%, P = 0.655). Time to AR was 11 months (95% confidence interval [CI], 8–15 months). After a median follow-up of 16 months (95% CI, 10–25 months), responders to reinduction had a median progression-free survival of 14 months (95% CI, 13, NR months), and in the whole cohort, the median overall survival from reinduction was 17 months (95% CI, 12–NR months). Twenty-seven (58%) immune-related adverse events (irAEs) were reported; 18 (38%) were grade 3/4, and in 11 of 27 (40%), the same irAE observed during induction therapy recurred. Conclusions: Reinduction with ipilimumab ± anti–PD-1 has modest clinical activity. Clinicians should be attentive to the risk of irAEs, including recurrence of irAEs that occurred during induction therapy. Future studies are necessary to determine best management after resistance to combination immunotherapy. Highlights: Despite high response rates with combination immunotherapy, many later progress. Aside from BRAF/MEKi, there are no standard subsequent therapies available. The role of reinduction with ipilimumab (alone or in combination) is unclear. The response rate to reinduction was 26%, and the disease control rate was 45%. 38% had grade 3/4 toxicity, but only 40% of induction toxicities recurred.